The Dual Crisis: Antibiotic Resistance and the Discovery Void – A Review of Novel Therapeutic Strategies and Non-Traditional Approaches - Priyanshu Upadhyay; Ankit Maurya; Anand Prakash (International Journal of Antibiotics, 2026)
The global rise of antimicrobial resistance (AMR) has emerged as one of the most critical public health challenges of the 21st century, threatening to undermine decades of therapeutic success and rendering conventional antibiotic regimens increasingly ineffective. Parallel to the escalating resistance rates is a profound “discovery void,” characterised by a steep decline in the development of new antibiotic classes since the late 20th century. Together, these two interconnected crises create a dual burden that significantly restricts treatment options and increases morbidity, mortality, and economic costs worldwide. This review provides a comprehensive evaluation of the underlying drivers of antibiotic resistance, the stagnation of antimicrobial innovation, and the urgent need for novel therapeutics that bypass the limitations of conventional drug discovery. Further, this paper highlights emerging non- traditional approaches—including bacteriophage therapy, antimicrobial peptides, CRISPR- based antimicrobials, nanoparticles, host-directed therapies, microbiome modulation, and anti-virulence strategies—that offer promising avenues to combat resistant pathogens without accelerating selective pressure. A detailed analysis of technological innovations such as AI- driven drug discovery, metagenomic mining, synthetic biology, and immunotherapeutic advancements is also presented. By integrating classical and alternative strategies, this review underscores the importance of a multifaceted approach to addressing the dual crisis and revitalising the antibiotic development pipeline for sustainable global health.
Keywords: Antimicrobial peptides; Antimicrobial resistance (AMR); CRISPR antimicrobials; Drug discovery; Synthetic Biology; anti-virulence strategies; antibiotic resistance; bacteriophage therapy; discovery void; host-directed therapy; microbiome modulation; nanoparticle therapeutics; non-traditional antimicrobials; novel therapeutics